Hemispheric specialization for processing auditory nonspeech stimuli. - Jamison, H; Watkins, K; Bishop, D; Matthews, P (2006)
The left hemisphere specialization for speech perception might arise from asymmetries at more basic levels of auditory processing. In particular, it has been suggested that differences in "temporal" and "spectral" processing exist between the hemispheres. Here we used functional magnetic resonance imaging to test this hypothesis further. Fourteen healthy volunteers listened to sequences of alternating pure tones that varied in the temporal and spectral domains. Increased temporal variation was associated with activation in Heschl's gyrus (HG) bilaterally, whereas increased spectral variation activated the superior temporal gyrus (STG) bilaterally and right posterior superior temporal sulcus (STS). Responses to increased temporal variation were lateralized to the left hemisphere; this left lateralization was greater in posteromedial HG, which is presumed to correspond to the primary auditory cortex. Responses to increased spectral variation were lateralized to the right hemisphere specifically in the anterior STG and posterior STS. These findings are consistent with the notion that the hemispheres are differentially specialized for processing auditory stimuli even in the absence of linguistic information.